Impacts of tourism in the panama region of sri lanka: an econometric analysis of social impacts - Nisthar, S.; Vijayakumar, S. (The Sri lanka Journal of South Asian Studies, 2016)
This study aims to find the social impacts of tourism in the Panama region of Sri Lanka by using quantitative method. The area of this study is Panama region of Sri Lanka in the South Eastern coastal belt of Sri Lanka. The Panama region is composed of five areas such as Arugambay, Kudakalliya, Jalaldeen Square, Kottukal, and Panama. The data have been collected by using the Five Likert Scale questionnaire for the analysis in year 2016/2017. The sample size is 530 out of population of 10,548 at 5 percent for the quantitative analysis. The tools to analyze the data are Reliability Analysis, Factor Analysis, Correlation, Multiple Regression, Co-linearity Statistics, Residual Analysis using SPSS 20.0. The dependent variable is Total Effect of tourism. Pride for Residence, Better Utility Services, Infrastructural Facilities, Living Standard, Entertainment, Interactions with Foreign Tourists are identified and used as the independent variables of the positive social impacts. As per the test of regression, all the independent variables are positively related with the dependent variable and statistically significant. As per the correlation analysis, the strength of positive linear association ship, the significance, and the direction of the independent and dependent variables confirm all the positive social impacts. The most influencing factor of the positive social impacts of tourism is Entertainment.
Keywords: Social impacts; Tourism; Panama Region; Factor Analysis; Regression